Aseptic meningitis after amenamevir treatment for herpes zoster ophthalmicus with oculomotor nerve palsy in a patient taking immunosuppressant. Issue 5 (May 2023) - Omiya, Moeko; Nishiguchi, Sho; Moriya, Hidekazu; Akazawa, Kenichiro; Nagahiro, Takanori; Seto, Masami
Abstract: A 79-year-old woman presented with vomiting after being prescribed amenamevir by her primary care physician. She had a medical history of rheumatoid arthritis and was administered prednisolone and methotrexate. She was finally diagnosed with herpes zoster ophthalmicus and aseptic meningitis, and intravenous antiviral therapy was initiated. However, the patient developed oculomotor nerve palsy on the 11th day of hospitalization. In this case, there was a time lag between the administration of antiviral drugs and clinical improvement. Our case suggests the necessity of selecting antivirals, especially in high-risk cases of CNS complications, to avoid the low intracerebral transferability of antiviral drugs, including amenamevir.